Molecular dynamics simulations of human α-thrombin in different structural contexts: evidence for an aptamer-guided cooperation between the two exosites. Issue 6 (31st March 2021) - Troisi, Romualdo; Balasco, Nicole; Vitagliano, Luigi; Sica, Filomena
Abstract: Human α-thrombin (thrombin) is a multifunctional enzyme that plays a pivotal role in the coagulation pathway. Thrombin activity can be effectively modulated by G-quadruplex-based oligonucleotide aptamers that specifically interact with the two positively charged regions (exosites I and II) on the protein surface. Although insightful atomic-level snapshots of the recognition between thrombin and aptamers have been recently achieved through crystallographic analyses, some dynamic aspects of this interaction have not been fully characterized. We here report molecular dynamics simulations of thrombin in different association states: ligand-free and binary/ternary complexes with the aptamers TBA (at exosite I) and HD22_27mer (at exosite II). The simulations carried out on the binary and ternary complexes formed by thrombin with these aptamers provide a dynamic view of the interactions that stabilize them in a crystal-free environment. Interestingly, the analysis of the dynamics of the exosites in different thrombin binding states clearly indicates that the HD22_27mer binding at the exosite II favours conformations of exosite I that are prone to the TBA binding. Similar effects are observed upon the binding of TBA to the exosite I. These observations provide an atomic-level picture of the exosite inter-communication in thrombin and explain the experimentally detected cooperativity of the TBA/HD22_27mer binding. Graphical Abstract: Communicated by Ramaswamy H. Sarma